2016
DOI: 10.1158/0008-5472.can-15-1010
|View full text |Cite
|
Sign up to set email alerts
|

Non–Small Cell Lung Cancer Cells Acquire Resistance to the ALK Inhibitor Alectinib by Activating Alternative Receptor Tyrosine Kinases

Abstract: Crizotinib is the standard of care for advanced non-small cell lung cancer (NSCLC) patients harboring the anaplastic lymphoma kinase (ALK) fusion gene, but resistance invariably develops. Unlike crizotinib, alectinib is a selective ALK tyrosine kinase inhibitor (TKI) with more potent antitumor effects and a favorable toxicity profile, even in crizotinib-resistant cases. However, acquired resistance to alectinib, as for other TKIs, remains a limitation of its efficacy. Therefore, we investigated the mechanisms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 39 publications
4
82
0
Order By: Relevance
“…Using TrkAi as a monotherapy or combined with low concentrations of CHOP hindered the growth of the lymphoma tumors in vivo and improved mice survival. Although selective ALK inhibitors represent an emerging strategy to treat ALK + neoplasms including NPM‐ALK + T‐cell lymphoma (Mosse et al ., 2013), several resistance mechanisms to these inhibitors have been already identified and characterized, which represents an important limitation (Dong et al ., 2016; Isozaki et al ., 2016; Katayama et al ., 2016; Zdzalik et al ., 2014). Our findings suggest that TrkA inhibition could represent an alternative therapeutic approach to tackle this aggressive neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Using TrkAi as a monotherapy or combined with low concentrations of CHOP hindered the growth of the lymphoma tumors in vivo and improved mice survival. Although selective ALK inhibitors represent an emerging strategy to treat ALK + neoplasms including NPM‐ALK + T‐cell lymphoma (Mosse et al ., 2013), several resistance mechanisms to these inhibitors have been already identified and characterized, which represents an important limitation (Dong et al ., 2016; Isozaki et al ., 2016; Katayama et al ., 2016; Zdzalik et al ., 2014). Our findings suggest that TrkA inhibition could represent an alternative therapeutic approach to tackle this aggressive neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…As explained for brigatinib, its double activity upon ALK and EGFR signaling could be useful when the second is involved in resistance mechanisms. The recently reported activation of c-MET, HER-3 and IGF-1R pathways in alectinib-resistant ALK-rearranged cells lines rise the issue of combined molecular treatments addressing to tumor-tailored biologic alterations (117). The latter concept has already been approached in in vitro pharmacological screens (118) and could be applicable in ALK-positive tumors where KRAS activation is the putative responsible of treatment resistance and clinical progression, with the putative double blockade (ALK and MEK inhibition) in a melanomaoriented fashion.…”
Section: Positioning In Clinical Practicementioning
confidence: 99%
“…Because of their benefits over other therapies, ALK tyrosine kinase inhibitors (ALK TKIs) are used as the chemotherapeutic agents of choice in NSCLC with ALK rearrangement (6). However, most cases receiving ALK inhibitors relapse within a few years after starting therapy (7)(8)(9)(10). Ongoing research mainly attempts to develop new small molecule inhibitors with greater potency against ALK and activity against acquired mutations (11).…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing research mainly attempts to develop new small molecule inhibitors with greater potency against ALK and activity against acquired mutations (11). Unfortunately, the second and third generation ALK inhibitors also show failure (8,12). Several studies have suggested that the combination of two or more therapeutic treatments is more effective than treatment with ALK TKI alone.…”
Section: Introductionmentioning
confidence: 99%